PREDICTIVE ANALYSIS OF WORK INCIDENT TROUGH SAFETY BEHAVIOR AND SAFETY CAPACITY - Adi Winarto, Ponco
Oil and gas energy still demanding today and keep as the most energy resources to support world activities. Maintaining top safety performance is one of key factor to keep company reputation. In Rokan Petroleum, it this still challenges to achieve incident free operation in the past 5 years, since 2015. The incident rate in Hole and Flow department showed declining trend by year but start to steadily increase in March 2019. Introducing new approach by analyze safety behavior on site expected could understand team safety performance to predict incident or nearmiss event in the future.